Homework 7
1. Find the determinant of the matrices using Gaussian elimination.
(a) [ 2 0 3 1 3 1 0 1 1 ] \begin{bmatrix} 2 & 0 & 3 \\ 1 & 3 & 1 \\ 0 & 1 & 1\end{bmatrix} 2 1 0 0 3 1 3 1 1
det [ 2 0 3 1 3 1 0 1 1 ] = R 2 − R 3 ∣ 2 0 3 1 2 0 0 1 1 ∣ = R 1 ↔ R 2 ( − 1 ) ∣ 1 2 0 2 0 3 0 1 1 ∣ = R 2 − 2 R 1 ( − 1 ) ∣ 1 2 0 0 − 4 3 0 1 1 ∣ = R 2 + 5 R 1 ( − 1 ) ∣ 1 2 0 0 1 8 0 1 1 ∣ = R 3 − R 2 ( − 1 ) ∣ 1 2 0 0 1 8 0 0 − 7 ∣ = ( − 1 ) ( 1 ⋅ 1 ⋅ − 7 ) = 7 \begin{align*}
\det\begin{bmatrix}
2 & 0 & 3 \\
1 & 3 & 1 \\
0 & 1 & 1
\end{bmatrix}
&\overset{R_2-R_3}{=}
\begin{vmatrix}
2 & 0 & 3 \\
1 & 2 & 0 \\
0 & 1 & 1
\end{vmatrix} \\
&\overset{R_1\leftrightarrow R_2}{=}
(-1)\begin{vmatrix}
1 & 2 & 0 \\
2 & 0 & 3 \\
0 & 1 & 1
\end{vmatrix} \\
&\overset{R_2 - 2R_1}{=}
(-1)\begin{vmatrix}
1 & 2 & 0 \\
0 & -4 & 3 \\
0 & 1 & 1
\end{vmatrix} \\
&\overset{R_2 + 5R_1}{=}
(-1)\begin{vmatrix}
1 & 2 & 0 \\
0 & 1 & 8 \\
0 & 1 & 1
\end{vmatrix} \\
&\overset{R_3 - R_2}{=}
(-1)\begin{vmatrix}
1 & 2 & 0 \\
0 & 1 & 8 \\
0 & 0 & -7
\end{vmatrix} \\
&= (-1)(1\cdot1\cdot-7) \\
&= 7
\end{align*} det 2 1 0 0 3 1 3 1 1 = R 2 − R 3 2 1 0 0 2 1 3 0 1 = R 1 ↔ R 2 ( − 1 ) 1 2 0 2 0 1 0 3 1 = R 2 − 2 R 1 ( − 1 ) 1 0 0 2 − 4 1 0 3 1 = R 2 + 5 R 1 ( − 1 ) 1 0 0 2 1 1 0 8 1 = R 3 − R 2 ( − 1 ) 1 0 0 2 1 0 0 8 − 7 = ( − 1 ) ( 1 ⋅ 1 ⋅ − 7 ) = 7
(b) [ 0 1 2 − 1 1 3 2 − 2 0 ] \begin{bmatrix} 0 & 1 & 2 \\ −1 & 1 & 3 \\ 2 & −2 & 0\end{bmatrix} 0 − 1 2 1 1 − 2 2 3 0
det [ 0 1 2 − 1 1 3 2 − 2 0 ] = R 1 ↔ R 2 ( − 1 ) ∣ − 1 1 3 0 1 2 2 − 2 0 ∣ = R 3 + 2 R 2 ( − 1 ) ∣ − 1 1 3 0 1 2 0 0 6 ∣ = ( − 1 ) ( − 1 ⋅ 1 ⋅ 6 ) = 6 \begin{align*}
\det\begin{bmatrix}
0 & 1 & 2 \\
−1 & 1 & 3 \\
2 & −2 & 0
\end{bmatrix}
&\overset{R_1\leftrightarrow R_2}{=}
(-1) \begin{vmatrix}
−1 & 1 & 3 \\
0 & 1 & 2 \\
2 & −2 & 0
\end{vmatrix} \\
&\overset{R_3 + 2R_2}{=}
(-1) \begin{vmatrix}
−1 & 1 & 3 \\
0 & 1 & 2 \\
0 & 0 & 6
\end{vmatrix} \\
&= (-1) (-1\cdot1\cdot6) \\
&= 6
\end{align*} det 0 − 1 2 1 1 − 2 2 3 0 = R 1 ↔ R 2 ( − 1 ) − 1 0 2 1 1 − 2 3 2 0 = R 3 + 2 R 2 ( − 1 ) − 1 0 0 1 1 0 3 2 6 = ( − 1 ) ( − 1 ⋅ 1 ⋅ 6 ) = 6
(c) [ 1 − 1 1 1 1 − 1 − 1 0 1 2 0 − 2 2 0 2 1 ] \begin{bmatrix}1 & −1 & 1 & 1\\1 & −1 & −1 & 0\\1 & 2 & 0 & −2\\2 & 0 & 2 & 1\end{bmatrix} 1 1 1 2 − 1 − 1 2 0 1 − 1 0 2 1 0 − 2 1
det [ 1 − 1 1 1 1 − 1 − 1 0 1 2 0 − 2 2 0 2 1 ] = R 2 − R 1 ∣ 1 − 1 1 1 0 0 − 2 − 1 1 2 0 − 2 2 0 2 1 ∣ = R 3 − R 1 ∣ 1 − 1 1 1 0 0 − 2 − 1 0 3 − 1 − 3 2 0 2 1 ∣ = R 4 − 2 R 1 ∣ 1 − 1 1 1 0 0 − 2 − 1 0 3 − 1 − 3 0 2 0 − 1 ∣ = R 2 ↔ R 3 ( − 1 ) ∣ 1 − 1 1 1 0 3 − 1 − 3 0 0 − 2 − 1 0 2 0 − 1 ∣ = 2 3 R 2 ( − 3 2 ) ∣ 1 − 1 1 1 0 2 − 2 3 − 2 0 0 − 2 − 1 0 2 0 − 1 ∣ = R 4 − R 2 ( − 3 2 ) ∣ 1 − 1 1 1 0 2 − 2 3 − 2 0 0 − 2 − 1 0 0 2 3 1 ∣ = 1 3 R 3 ( − 9 2 ) ∣ 1 − 1 1 1 0 2 − 2 3 − 2 0 0 − 2 3 − 1 3 0 0 2 3 1 ∣ = R 4 + R 3 ( − 9 2 ) ∣ 1 − 1 1 1 0 2 − 2 3 − 2 0 0 − 2 3 − 1 3 0 0 0 2 3 ∣ = ( − 9 2 ) ( 1 ⋅ 2 ⋅ − 2 3 ⋅ 2 3 ) = 4 \begin{align*}
\det\begin{bmatrix}
1 & −1 & 1 & 1 \\
1 & −1 & −1 & 0 \\
1 & 2 & 0 & −2 \\
2 & 0 & 2 & 1
\end{bmatrix}
&\overset{R_2 - R_1}{=}
\begin{vmatrix}
1 & −1 & 1 & 1 \\
0 & 0 & -2 & -1 \\
1 & 2 & 0 & −2 \\
2 & 0 & 2 & 1
\end{vmatrix} \\
&\overset{R_3 - R_1}{=}
\begin{vmatrix}
1 & −1 & 1 & 1 \\
0 & 0 & -2 & -1 \\
0 & 3 & -1 & −3 \\
2 & 0 & 2 & 1
\end{vmatrix} \\
&\overset{R_4 - 2R_1}{=}
\begin{vmatrix}
1 & −1 & 1 & 1 \\
0 & 0 & -2 & -1 \\
0 & 3 & -1 & −3 \\
0 & 2 & 0 & -1
\end{vmatrix} \\
&\overset{R_2\leftrightarrow R_3}{=}
(-1) \begin{vmatrix}
1 & −1 & 1 & 1 \\
0 & 3 & -1 & −3 \\
0 & 0 & -2 & -1 \\
0 & 2 & 0 & -1
\end{vmatrix} \\
&\overset{\frac{2}{3}R_2}{=}
\left(-\frac{3}{2}\right) \begin{vmatrix}
1 & −1 & 1 & 1 \\
0 & 2 & -\frac{2}{3} & -2 \\
0 & 0 & -2 & -1 \\
0 & 2 & 0 & -1
\end{vmatrix} \\
&\overset{R_4 - R_2}{=}
\left(-\frac{3}{2}\right) \begin{vmatrix}
1 & −1 & 1 & 1 \\
0 & 2 & -\frac{2}{3} & -2 \\
0 & 0 & -2 & -1 \\
0 & 0 & \frac{2}{3} & 1
\end{vmatrix} \\
&\overset{\frac{1}{3}R_3}{=}
\left(-\frac{9}{2}\right) \begin{vmatrix}
1 & −1 & 1 & 1 \\[.5em]
0 & 2 & -\frac{2}{3} & -2 \\[.5em]
0 & 0 & -\frac{2}{3} & -\frac{1}{3} \\[.5em]
0 & 0 & \frac{2}{3} & 1
\end{vmatrix} \\
&\overset{R_4 + R_3}{=}
\left(-\frac{9}{2}\right) \begin{vmatrix}
1 & −1 & 1 & 1 \\[.5em]
0 & 2 & -\frac{2}{3} & -2 \\[.5em]
0 & 0 & -\frac{2}{3} & -\frac{1}{3} \\[.5em]
0 & 0 & 0 & \frac{2}{3}
\end{vmatrix} \\
&= \left(-\frac{9}{2}\right)\left(1\cdot2\cdot-\frac{2}{3}\cdot\frac{2}{3}\right) \\
&= 4
\end{align*} det 1 1 1 2 − 1 − 1 2 0 1 − 1 0 2 1 0 − 2 1 = R 2 − R 1 1 0 1 2 − 1 0 2 0 1 − 2 0 2 1 − 1 − 2 1 = R 3 − R 1 1 0 0 2 − 1 0 3 0 1 − 2 − 1 2 1 − 1 − 3 1 = R 4 − 2 R 1 1 0 0 0 − 1 0 3 2 1 − 2 − 1 0 1 − 1 − 3 − 1 = R 2 ↔ R 3 ( − 1 ) 1 0 0 0 − 1 3 0 2 1 − 1 − 2 0 1 − 3 − 1 − 1 = 3 2 R 2 ( − 2 3 ) 1 0 0 0 − 1 2 0 2 1 − 3 2 − 2 0 1 − 2 − 1 − 1 = R 4 − R 2 ( − 2 3 ) 1 0 0 0 − 1 2 0 0 1 − 3 2 − 2 3 2 1 − 2 − 1 1 = 3 1 R 3 ( − 2 9 ) 1 0 0 0 − 1 2 0 0 1 − 3 2 − 3 2 3 2 1 − 2 − 3 1 1 = R 4 + R 3 ( − 2 9 ) 1 0 0 0 − 1 2 0 0 1 − 3 2 − 3 2 0 1 − 2 − 3 1 3 2 = ( − 2 9 ) ( 1 ⋅ 2 ⋅ − 3 2 ⋅ 3 2 ) = 4
(d)[ 2 1 1 1 1 1 2 1 1 1 1 1 2 1 1 1 1 1 2 1 1 1 1 1 2 ] \begin{bmatrix}2 & 1 & 1 & 1 & 1 \\1 & 2 & 1 & 1 & 1 \\1 & 1 & 2 & 1 & 1 \\1 & 1 & 1 & 2 & 1 \\1 & 1 & 1 & 1 & 2\end{bmatrix} 2 1 1 1 1 1 2 1 1 1 1 1 2 1 1 1 1 1 2 1 1 1 1 1 2
det [ 2 1 1 1 1 1 2 1 1 1 1 1 2 1 1 1 1 1 2 1 1 1 1 1 2 ] = R 1 ↔ R 2 ( − 1 ) ∣ 1 2 1 1 1 2 1 1 1 1 1 1 2 1 1 1 1 1 2 1 1 1 1 1 2 ∣ = R 2 − 2 R 1 ( − 1 ) ∣ 1 2 1 1 1 0 − 3 − 1 − 1 − 1 1 1 2 1 1 1 1 1 2 1 1 1 1 1 2 ∣ = R 3 − R 1 R 4 − R 1 R 5 − R 1 ( − 1 ) ∣ 1 2 1 1 1 0 − 3 − 1 − 1 − 1 0 − 1 1 0 0 0 − 1 0 1 0 0 − 1 0 0 1 ∣ = R 2 ↔ R 3 ∣ 1 2 1 1 1 0 − 1 1 0 0 0 − 3 − 1 − 1 − 1 0 − 1 0 1 0 0 − 1 0 0 1 ∣ = R 3 − 3 R 2 ∣ 1 2 1 1 1 0 − 1 1 0 0 0 0 − 4 − 1 − 1 0 − 1 0 1 0 0 − 1 0 0 1 ∣ = R 4 − R 2 R 5 − R 2 ∣ 1 2 1 1 1 0 − 1 1 0 0 0 0 − 4 − 1 − 1 0 0 − 1 1 0 0 0 − 1 0 1 ∣ = R 3 ↔ R 4 ( − 1 ) ∣ 1 2 1 1 1 0 − 1 1 0 0 0 0 − 1 1 0 0 0 − 4 − 1 − 1 0 0 − 1 0 1 ∣ = R 4 − 4 R 3 ( − 1 ) ∣ 1 2 1 1 1 0 − 1 1 0 0 0 0 − 1 1 0 0 0 0 − 5 − 1 0 0 − 1 0 1 ∣ = R 5 − R 3 ( − 1 ) ∣ 1 2 1 1 1 0 − 1 1 0 0 0 0 − 1 1 0 0 0 0 − 5 − 1 0 0 0 − 1 1 ∣ = R 4 ↔ R 5 ∣ 1 2 1 1 1 0 − 1 1 0 0 0 0 − 1 1 0 0 0 0 − 1 1 0 0 0 − 5 − 1 ∣ = R 5 − 5 R 4 ∣ 1 2 1 1 1 0 − 1 1 0 0 0 0 − 1 1 0 0 0 0 − 1 1 0 0 0 0 − 6 ∣ = 1 ⋅ − 1 ⋅ − 1 ⋅ − 1 ⋅ − 6 = 6 \begin{align*}
\det\begin{bmatrix}
2 & 1 & 1 & 1 & 1 \\
1 & 2 & 1 & 1 & 1 \\
1 & 1 & 2 & 1 & 1 \\
1 & 1 & 1 & 2 & 1 \\
1 & 1 & 1 & 1 & 2
\end{bmatrix}
&\overset{R_1\leftrightarrow R_2}{=}
(-1)\begin{vmatrix}
1 & 2 & 1 & 1 & 1 \\
2 & 1 & 1 & 1 & 1 \\
1 & 1 & 2 & 1 & 1 \\
1 & 1 & 1 & 2 & 1 \\
1 & 1 & 1 & 1 & 2
\end{vmatrix} \\
&\overset{R_2 - 2R_1}{=}
(-1)\begin{vmatrix}
1 & 2 & 1 & 1 & 1 \\
0 & -3 & -1 & -1 & -1 \\
1 & 1 & 2 & 1 & 1 \\
1 & 1 & 1 & 2 & 1 \\
1 & 1 & 1 & 1 & 2
\end{vmatrix} \\
&\overset{\substack{R_3 - R_1 \\ R_4 - R_1 \\ R_5 - R_1}}{=}
(-1)\begin{vmatrix}
1 & 2 & 1 & 1 & 1 \\
0 & -3 & -1 & -1 & -1 \\
0 & -1 & 1 & 0 & 0 \\
0 & -1 & 0 & 1 & 0 \\
0 & -1 & 0 & 0 & 1
\end{vmatrix} \\
&\overset{R_2\leftrightarrow R_3}{=}
\begin{vmatrix}
1 & 2 & 1 & 1 & 1 \\
0 & -1 & 1 & 0 & 0 \\
0 & -3 & -1 & -1 & -1 \\
0 & -1 & 0 & 1 & 0 \\
0 & -1 & 0 & 0 & 1
\end{vmatrix} \\
&\overset{R_3 - 3R_2}{=}
\begin{vmatrix}
1 & 2 & 1 & 1 & 1 \\
0 & -1 & 1 & 0 & 0 \\
0 & 0 & -4 & -1 & -1 \\
0 & -1 & 0 & 1 & 0 \\
0 & -1 & 0 & 0 & 1
\end{vmatrix} \\
&\overset{\substack{R_4 - R_2 \\ R_5 - R_2}}{=}
\begin{vmatrix}
1 & 2 & 1 & 1 & 1 \\
0 & -1 & 1 & 0 & 0 \\
0 & 0 & -4 & -1 & -1 \\
0 & 0 & -1 & 1 & 0 \\
0 & 0 & -1 & 0 & 1
\end{vmatrix} \\
&\overset{R_3 \leftrightarrow R_4}{=}
(-1)\begin{vmatrix}
1 & 2 & 1 & 1 & 1 \\
0 & -1 & 1 & 0 & 0 \\
0 & 0 & -1 & 1 & 0 \\
0 & 0 & -4 & -1 & -1 \\
0 & 0 & -1 & 0 & 1
\end{vmatrix} \\
&\overset{R_4 - 4R_3}{=}
(-1)\begin{vmatrix}
1 & 2 & 1 & 1 & 1 \\
0 & -1 & 1 & 0 & 0 \\
0 & 0 & -1 & 1 & 0 \\
0 & 0 & 0 & -5 & -1 \\
0 & 0 & -1 & 0 & 1
\end{vmatrix} \\
&\overset{R_5 - R_3}{=}
(-1)\begin{vmatrix}
1 & 2 & 1 & 1 & 1 \\
0 & -1 & 1 & 0 & 0 \\
0 & 0 & -1 & 1 & 0 \\
0 & 0 & 0 & -5 & -1 \\
0 & 0 & 0 & -1 & 1
\end{vmatrix} \\
&\overset{R_4 \leftrightarrow R_5}{=}
\begin{vmatrix}
1 & 2 & 1 & 1 & 1 \\
0 & -1 & 1 & 0 & 0 \\
0 & 0 & -1 & 1 & 0 \\
0 & 0 & 0 & -1 & 1 \\
0 & 0 & 0 & -5 & -1 \\
\end{vmatrix} \\
&\overset{R_5 - 5R_4}{=}
\begin{vmatrix}
1 & 2 & 1 & 1 & 1 \\
0 & -1 & 1 & 0 & 0 \\
0 & 0 & -1 & 1 & 0 \\
0 & 0 & 0 & -1 & 1 \\
0 & 0 & 0 & 0 & -6 \\
\end{vmatrix} \\
&= 1\cdot-1\cdot-1\cdot-1\cdot-6 \\
&= 6
\end{align*} det 2 1 1 1 1 1 2 1 1 1 1 1 2 1 1 1 1 1 2 1 1 1 1 1 2 = R 1 ↔ R 2 ( − 1 ) 1 2 1 1 1 2 1 1 1 1 1 1 2 1 1 1 1 1 2 1 1 1 1 1 2 = R 2 − 2 R 1 ( − 1 ) 1 0 1 1 1 2 − 3 1 1 1 1 − 1 2 1 1 1 − 1 1 2 1 1 − 1 1 1 2 = R 3 − R 1 R 4 − R 1 R 5 − R 1 ( − 1 ) 1 0 0 0 0 2 − 3 − 1 − 1 − 1 1 − 1 1 0 0 1 − 1 0 1 0 1 − 1 0 0 1 = R 2 ↔ R 3 1 0 0 0 0 2 − 1 − 3 − 1 − 1 1 1 − 1 0 0 1 0 − 1 1 0 1 0 − 1 0 1 = R 3 − 3 R 2 1 0 0 0 0 2 − 1 0 − 1 − 1 1 1 − 4 0 0 1 0 − 1 1 0 1 0 − 1 0 1 = R 4 − R 2 R 5 − R 2 1 0 0 0 0 2 − 1 0 0 0 1 1 − 4 − 1 − 1 1 0 − 1 1 0 1 0 − 1 0 1 = R 3 ↔ R 4 ( − 1 ) 1 0 0 0 0 2 − 1 0 0 0 1 1 − 1 − 4 − 1 1 0 1 − 1 0 1 0 0 − 1 1 = R 4 − 4 R 3 ( − 1 ) 1 0 0 0 0 2 − 1 0 0 0 1 1 − 1 0 − 1 1 0 1 − 5 0 1 0 0 − 1 1 = R 5 − R 3 ( − 1 ) 1 0 0 0 0 2 − 1 0 0 0 1 1 − 1 0 0 1 0 1 − 5 − 1 1 0 0 − 1 1 = R 4 ↔ R 5 1 0 0 0 0 2 − 1 0 0 0 1 1 − 1 0 0 1 0 1 − 1 − 5 1 0 0 1 − 1 = R 5 − 5 R 4 1 0 0 0 0 2 − 1 0 0 0 1 1 − 1 0 0 1 0 1 − 1 0 1 0 0 1 − 6 = 1 ⋅ − 1 ⋅ − 1 ⋅ − 1 ⋅ − 6 = 6
2. Given 5 × 5 5\times5 5 × 5 matrices A A A , B B B , Q Q Q . Suppose that det A = 3 \det A = 3 det A = 3 , det B = 2 \det B = 2 det B = 2 and Q Q Q is an invertible matrix. Find the determinant of A T B A^TB A T B , A 3 A^3 A 3 , 2 A 2A 2 A , A B A ABA A B A and Q − 1 A Q Q^{−1}AQ Q − 1 A Q .
det A T B \det A^T B det A T B
det A T B = det A T det B = det A det B = 3 ⋅ 2 = 6 \begin{align*}
\det A^T B &= \det A^T \det B \\
&= \det A \det B \\
&= 3\cdot 2 \\
&= 6
\end{align*} det A T B = det A T det B = det A det B = 3 ⋅ 2 = 6
det A 3 \det A^3 det A 3
det A 3 = det A A A = det A det A det A = 3 ⋅ 3 ⋅ 3 = 27 \begin{align*}
\det A^3 &= \det AAA \\
&= \det A \det A \det A \\
&= 3\cdot3\cdot3 \\
&= 27
\end{align*} det A 3 = det AAA = det A det A det A = 3 ⋅ 3 ⋅ 3 = 27
det 2 A \det 2A det 2 A
det 2 A = det 2 ( a 11 ⋱ a 55 ) , a i j ∈ R = det ( 2 a 11 ⋱ 2 a 55 ) , a i j ∈ R = 2 5 det ( a 11 ⋱ a 55 ) , a i j ∈ R = 2 5 det A = 32 ⋅ 3 = 96 \begin{align*}
\det 2A &= \det 2\begin{pmatrix}
a_{11} & & \\
&\ddots& \\
& & a_{55}
\end{pmatrix}, & a_{ij} \in \R \\
&= \det \begin{pmatrix}
2a_{11} & & \\
&\ddots& \\
& & 2a_{55}
\end{pmatrix}, & a_{ij} \in \R \\
&= 2^5 \det \begin{pmatrix}
a_{11} & & \\
&\ddots& \\
& & a_{55}
\end{pmatrix}, & a_{ij} \in \R \\
&= 2^5 \det A \\
&= 32 \cdot 3 \\
&= 96
\end{align*} det 2 A = det 2 a 11 ⋱ a 55 , = det 2 a 11 ⋱ 2 a 55 , = 2 5 det a 11 ⋱ a 55 , = 2 5 det A = 32 ⋅ 3 = 96 a ij ∈ R a ij ∈ R a ij ∈ R
det A B A \det ABA det A B A
det A B A = det A det B det A = 3 ⋅ 2 ⋅ 3 = 18 \begin{align*}
\det ABA &= \det A \det B \det A \\
&= 3 \cdot 2 \cdot 3 \\
&= 18
\end{align*} det A B A = det A det B det A = 3 ⋅ 2 ⋅ 3 = 18
det Q − 1 A Q \det Q^{-1}AQ det Q − 1 A Q
det Q − 1 A Q = det Q − 1 det A det Q = 1 det Q det A det Q = det A = 3 \begin{align*}
\det Q^{-1}AQ &= \det Q^{-1} \det A \det Q \\
&= \frac{1}{\det Q} \det A \det Q \\
&= \det A \\
&= 3
\end{align*} det Q − 1 A Q = det Q − 1 det A det Q = det Q 1 det A det Q = det A = 3
3. Consider the following system of linear equations: { p x + y + z = 6 , 3 x − y + 11 z = 6 , 2 x + y + 4 z = q , \begin{cases} px + y + z = 6, \\ 3x − y + 11z = 6, \\ 2x + y + 4z = q,\end{cases} ⎩ ⎨ ⎧ p x + y + z = 6 , 3 x − y + 11 z = 6 , 2 x + y + 4 z = q ,
(a) Find the condition on p p p so that the system has unique solution (Hint: det ( A ) ≠ 0 \det(A) \neq 0 det ( A ) = 0 ).
{ p x + y + z 3 x − y + 11 z 2 x + y + 4 z ⟺ ( p 1 1 3 − 1 11 2 1 4 ) det ( p 1 1 3 − 1 11 2 1 4 ) = p ∣ − 1 11 1 4 ∣ − ∣ 3 11 2 4 ∣ + ∣ 3 − 1 2 1 ∣ = p ( − 4 − 11 ) − ( 12 − 22 ) + ( 3 − ( − 2 ) ) = − 15 p + 15 ∴ det ( p 1 1 3 − 1 11 2 1 4 ) ≠ 0 ⟺ p ≠ 1 \begin{cases}
px + y + z \\
3x − y + 11z \\
2x + y + 4z
\end{cases}
\iff \begin{pmatrix}
p & 1 & 1 \\
3 & -1 & 11 \\
2 & 1 & 4
\end{pmatrix}
\\
\begin{align*}
\det \begin{pmatrix}
p & 1 & 1 \\
3 & -1 & 11 \\
2 & 1 & 4
\end{pmatrix} &= p \begin{vmatrix}
-1 & 11 \\
1 & 4
\end{vmatrix}
- \begin{vmatrix}
3 & 11 \\
2 & 4
\end{vmatrix}
+ \begin{vmatrix}
3 & -1 \\
2 & 1
\end{vmatrix} \\
&= p(-4-11) - (12-22) + (3-(-2)) \\
&= -15p + 15
\end{align*}
\\
\therefore \det\begin{pmatrix}
p & 1 & 1 \\
3 & -1 & 11 \\
2 & 1 & 4
\end{pmatrix} \neq 0 \iff p \neq 1 ⎩ ⎨ ⎧ p x + y + z 3 x − y + 11 z 2 x + y + 4 z ⟺ p 3 2 1 − 1 1 1 11 4 det p 3 2 1 − 1 1 1 11 4 = p − 1 1 11 4 − 3 2 11 4 + 3 2 − 1 1 = p ( − 4 − 11 ) − ( 12 − 22 ) + ( 3 − ( − 2 )) = − 15 p + 15 ∴ det p 3 2 1 − 1 1 1 11 4 = 0 ⟺ p = 1
As such, the system has unique solution for all p ≠ 1 p\neq1 p = 1 .
(b) Find the condition on p p p and q q q so that the system has infinitely many solutions (Hint: det ( A ) = 0 \det(A) = 0 det ( A ) = 0 and no inconsistent equations). Describe the solution set.
{ p x + y + z = 6 3 x − y + 11 z = 6 2 x + y + 4 z = q ⟺ ( p 1 1 6 3 − 1 11 6 2 1 4 q ) \begin{cases}
px + y + z = 6 \\
3x − y + 11z = 6 \\
2x + y + 4z = q
\end{cases}
\iff
\left(
\begin{array}{ccc|c}
p & 1 & 1 & 6 \\
3 & -1 & 11 & 6 \\
2 & 1 & 4 & q
\end{array}
\right) ⎩ ⎨ ⎧ p x + y + z = 6 3 x − y + 11 z = 6 2 x + y + 4 z = q ⟺ p 3 2 1 − 1 1 1 11 4 6 6 q
From (a), we know that det ( p 1 1 3 − 1 11 2 1 4 ) = 0 ⟺ p = 1 \det\begin{pmatrix}
p & 1 & 1 \\
3 & -1 & 11 \\
2 & 1 & 4
\end{pmatrix} = 0 \iff p = 1 det p 3 2 1 − 1 1 1 11 4 = 0 ⟺ p = 1 . So, we can just Gaussian with p = 1 p=1 p = 1 .
( 1 1 1 6 3 − 1 11 6 2 1 4 q ) → R 3 − 2 R 1 R 2 − 3 R 1 ( 1 1 1 6 0 − 4 8 − 12 0 − 1 2 q − 12 ) → − 1 4 R 2 ( 1 1 1 6 0 1 − 2 3 0 − 1 2 q − 12 ) → R 3 + R 2 ( 1 1 1 6 0 1 − 2 3 0 0 0 q − 9 ) \begin{array}{c}
\left(
\begin{array}{ccc|c}
1 & 1 & 1 & 6 \\
3 & -1 & 11 & 6\\
2 & 1 & 4 & q
\end{array}
\right)
&\xrightarrow[R_3 - 2R_1]{R_2 - 3R_1}
&\left(
\begin{array}{ccc|c}
1 & 1 & 1 & 6 \\
0 & -4 & 8 & -12 \\
0 & -1 & 2 & q-12
\end{array}
\right) \\
&\xrightarrow{-\frac{1}{4}R_2}
&\left(
\begin{array}{ccc|c}
1 & 1 & 1 & 6 \\
0 & 1 & -2 & 3 \\
0 & -1 & 2 & q-12
\end{array}
\right) \\
&\xrightarrow{R_3 + R_2}
&\left(
\begin{array}{ccc|c}
1 & 1 & 1 & 6 \\
0 & 1 & -2 & 3 \\
0 & 0 & 0 & q-9
\end{array}
\right)
\end{array} 1 3 2 1 − 1 1 1 11 4 6 6 q R 2 − 3 R 1 R 3 − 2 R 1 − 4 1 R 2 R 3 + R 2 1 0 0 1 − 4 − 1 1 8 2 6 − 12 q − 12 1 0 0 1 1 − 1 1 − 2 2 6 3 q − 12 1 0 0 1 1 0 1 − 2 0 6 3 q − 9
Here, we see that the last row is 0 = q − 9 0 = q-9 0 = q − 9 . As such, the system will have a consistent solution if and only if q = 9 q=9 q = 9 .
To get the solution set, we continue to Gaussian to obtain the reduced-row echelon form.
( 1 1 1 6 0 1 − 2 3 0 0 0 q − 9 ) → R 1 − R 2 ( 1 0 3 3 0 1 − 2 3 0 0 0 q − 9 ) ∴ y = 2 z + 3 x = − 3 z + 3 \begin{array}{c}
\left(
\begin{array}{ccc|c}
1 & 1 & 1 & 6 \\
0 & 1 & -2 & 3 \\
0 & 0 & 0 & q-9
\end{array}
\right)
&\xrightarrow{R_1 - R_2}
&\left(
\begin{array}{ccc|c}
1 & 0 & 3 & 3 \\
0 & 1 & -2 & 3 \\
0 & 0 & 0 & q-9
\end{array}
\right)
\end{array}
\\
\therefore y = 2z + 3 \\
x = -3z + 3 1 0 0 1 1 0 1 − 2 0 6 3 q − 9 R 1 − R 2 1 0 0 0 1 0 3 − 2 0 3 3 q − 9 ∴ y = 2 z + 3 x = − 3 z + 3
Therefore, the system
{ p x + y + z = 6 3 x − y + 11 z = 6 2 x + y + 4 z = q \begin{cases}
px + y + z = 6 \\
3x − y + 11z = 6 \\
2x + y + 4z = q
\end{cases} ⎩ ⎨ ⎧ p x + y + z = 6 3 x − y + 11 z = 6 2 x + y + 4 z = q
contains infinitely many solutions if and only if p = 1 p=1 p = 1 and q = 9 q=9 q = 9 , for which its solution set is
{ ( x , y , z ) : ( − 3 z + 3 2 z + 3 z ) : z ∈ R } . \Set{
(x,y,z): \begin{pmatrix}
-3z + 3 \\
2z + 3 \\
z
\end{pmatrix}: z\in\R
}. ⎩ ⎨ ⎧ ( x , y , z ) : − 3 z + 3 2 z + 3 z : z ∈ R ⎭ ⎬ ⎫ .
4. Show that if A A A is an n × n n \times n n × n skew-symmetric matrix (i.e. A T = − A A^T = −A A T = − A ) and n n n is an odd number, then det A = 0 \det A = 0 det A = 0 .
Given that det A T = det A \det A^T = \det A det A T = det A . Then if A T = − A A^T = -A A T = − A (A A A is skew-symmetric), we have that:
det A T = det A = det ( − A ) \det A^T = \det A = \det (-A) det A T = det A = det ( − A )
If n n n is odd, then n = k + 1 n=k+1 n = k + 1 for k ∈ N k\in\N k ∈ N . As such:
det ( − A ) = det − 1 ⋅ ( a 11 ⋱ a n n ) , a i j ∈ R = det ( ( − 1 ) a 11 ⋱ ( − 1 ) a n n ) , a i j ∈ R = ( − 1 ) n det ( a 11 ⋱ a n n ) , a i j ∈ R = ( − 1 ) k + 1 det A n = k + 1 = − det A ( − 1 ) k + 1 = − 1 ∀ k ∈ N \begin{align*}
\det(-A) &= \det -1\cdot\begin{pmatrix}
a_{11} & & \\
& \ddots & \\
& & a_{nn}
\end{pmatrix}, &a_{ij}\in\R \\
&= \det\begin{pmatrix}
(-1)a_{11} & & \\
& \ddots & \\
& & (-1)a_{nn}
\end{pmatrix}, &a_{ij}\in\R \\
&= (-1)^n\det\begin{pmatrix}
a_{11} & & \\
& \ddots & \\
& & a_{nn}
\end{pmatrix}, &a_{ij}\in\R \\
&= (-1)^{k+1}\det A & \boxed{n=k+1}\\
&= -\det A & \boxed{(-1)^{k+1} = -1\quad\forall k\in\N}
\end{align*} det ( − A ) = det − 1 ⋅ a 11 ⋱ a nn , = det ( − 1 ) a 11 ⋱ ( − 1 ) a nn , = ( − 1 ) n det a 11 ⋱ a nn , = ( − 1 ) k + 1 det A = − det A a ij ∈ R a ij ∈ R a ij ∈ R n = k + 1 ( − 1 ) k + 1 = − 1 ∀ k ∈ N
Since det A T = det A = det ( − A ) = − det A \det A^T = \det A = \det(-A) = -\det A det A T = det A = det ( − A ) = − det A . Then, det A = − det A ⟺ det A = 0 \det A = -\det A \iff \det A = 0 det A = − det A ⟺ det A = 0 .
5. Let A = [ 1 3 4 2 ] , B = [ 0 − 2 − 3 − 1 1 − 1 2 2 5 ] . A = \begin{bmatrix} 1 & 3 \\ 4 & 2\end{bmatrix},\quad B =\begin{bmatrix} 0 & −2 & −3 \\ −1 & 1 & −1 \\ 2 & 2 & 5\end{bmatrix}. A = [ 1 4 3 2 ] , B = 0 − 1 2 − 2 1 2 − 3 − 1 5 .
(i) Find the eigenvalues and eigenvectors of both A A A and B B B .
Eigenvalues and eigenvectors for A A A
det ( A − λ I ) = ∣ 1 − λ 3 4 2 − λ ∣ = 0 = ( 1 − λ ) ( 2 − λ ) − 12 = 0 = λ 2 − 3 λ − 10 = 0 = ( λ + 2 ) ( λ − 5 ) = 0 ∴ λ = − 2 , 5 \begin{align*}
\det (A-\lambda I) &= \begin{vmatrix}
1-\lambda & 3 \\
4 & 2-\lambda
\end{vmatrix} &= 0 \\
&= (1-\lambda)(2-\lambda) - 12 &= 0 \\
&= \lambda^2 - 3\lambda - 10 &= 0 \\
&= (\lambda + 2)(\lambda - 5) &= 0
\end{align*}
\\
\therefore\lambda = -2, 5 det ( A − λ I ) = 1 − λ 4 3 2 − λ = ( 1 − λ ) ( 2 − λ ) − 12 = λ 2 − 3 λ − 10 = ( λ + 2 ) ( λ − 5 ) = 0 = 0 = 0 = 0 ∴ λ = − 2 , 5
The eigenvalues of A A A are − 2 -2 − 2 and 5 5 5 .
λ = − 2 ⟹ A + 2 I A + 2 I = [ 3 3 4 4 ] ⟹ rref ( A + 2 I ) = [ 1 1 0 0 ] ∴ x 1 = − x 2 x 2 ∈ R ∴ ker ( A + 2 I ) = { ( − x 2 x 2 ) : x 2 ∈ R } = { x ( − 1 1 ) : x ∈ R } \lambda = -2 \implies A+2I \\
A + 2I = \begin{bmatrix}
3 & 3 \\
4 & 4
\end{bmatrix}
\implies\operatorname{rref}(A+2I) = \begin{bmatrix}
1 & 1 \\
0 & 0
\end{bmatrix} \\
\therefore x_1 = -x_2 \\
x_2\in\R
\\
\therefore\ker(A+2I) = \Set{
\begin{pmatrix}
-x_2 \\ x_2
\end{pmatrix}: x_2\in\R
}
= \Set{
x\begin{pmatrix}
-1 \\ 1
\end{pmatrix}: x\in\R
} λ = − 2 ⟹ A + 2 I A + 2 I = [ 3 4 3 4 ] ⟹ rref ( A + 2 I ) = [ 1 0 1 0 ] ∴ x 1 = − x 2 x 2 ∈ R ∴ ker ( A + 2 I ) = { ( − x 2 x 2 ) : x 2 ∈ R } = { x ( − 1 1 ) : x ∈ R }
An eigenvector corresponding to λ = − 2 \lambda=-2 λ = − 2 is ( − 1 1 ) \begin{pmatrix}
-1 \\ 1
\end{pmatrix} ( − 1 1 ) .
λ = 5 ⟹ A − 5 I A − 5 I = [ − 4 3 4 − 3 ] ⟹ rref ( A − 5 I ) = [ 1 − 3 4 0 0 ] ∴ x 1 = 3 4 x 2 x 2 ∈ R ∴ ker ( A − 5 I ) = { ( 3 4 x 2 x 2 ) : x 2 ∈ R } = { x ( 3 4 1 ) : x ∈ R } \lambda = 5 \implies A - 5I \\
A - 5I = \begin{bmatrix}
-4 & 3 \\
4 & -3
\end{bmatrix} \implies \operatorname{rref}(A-5I) = \begin{bmatrix}
1 & -\frac{3}{4} \\
0 & 0
\end{bmatrix} \\
\therefore x_1 = \frac{3}{4}x_2 \\
x_2 \in\R \\
\therefore\ker(A-5I) = \Set{
\begin{pmatrix}
\frac{3}{4}x_2 \\ x_2
\end{pmatrix}: x_2 \in\R
} = \Set{
x\begin{pmatrix}
\frac{3}{4} \\[.2em] 1
\end{pmatrix}: x\in\R
} λ = 5 ⟹ A − 5 I A − 5 I = [ − 4 4 3 − 3 ] ⟹ rref ( A − 5 I ) = [ 1 0 − 4 3 0 ] ∴ x 1 = 4 3 x 2 x 2 ∈ R ∴ ker ( A − 5 I ) = { ( 4 3 x 2 x 2 ) : x 2 ∈ R } = { x ( 4 3 1 ) : x ∈ R }
An eigenvector corresponding to λ = 5 \lambda=5 λ = 5 is ( 3 4 1 ) \begin{pmatrix}
\frac{3}{4} \\[.2em] 1
\end{pmatrix} ( 4 3 1 ) .
Eigenvalues and eigenvectors for B B B
det ( B − λ I ) = ∣ − λ − 2 − 3 − 1 1 − λ − 1 2 2 5 − λ ∣ = 0 = − λ ∣ 1 − λ − 1 2 5 − λ ∣ − ( − 2 ) ∣ − 1 − 1 2 5 − λ ∣ + ( − 3 ) ∣ − 1 1 − λ 2 2 ∣ = 0 = − λ ( λ 2 − 6 λ + 7 ) − ( − 2 ) ( λ − 3 ) + ( − 3 ) ( 2 λ − 4 ) = 0 = − λ 3 + 6 λ 2 − 11 λ + 6 = 0 = − ( λ − 3 ) ( λ − 2 ) ( λ − 1 ) = 0 ∴ λ = 1 , 2 , 3 \begin{align*}
\det(B-\lambda I) &= \begin{vmatrix}
-\lambda & −2 & −3 \\
−1 & 1-\lambda & −1 \\
2 & 2 & 5-\lambda
\end{vmatrix} &= 0 \\
&= -\lambda \begin{vmatrix}
1-\lambda & −1 \\
2 & 5-\lambda
\end{vmatrix} - (-2) \begin{vmatrix}
−1 & −1 \\
2 & 5-\lambda
\end{vmatrix} + (-3) \begin{vmatrix}
−1 & 1-\lambda \\
2 & 2
\end{vmatrix} &= 0 \\
&= -\lambda(\lambda^2 - 6\lambda + 7) -(-2)(\lambda-3) + (-3)(2\lambda-4) &= 0 \\
&= -\lambda^3 + 6\lambda^2 - 11\lambda + 6 &= 0 \\
&= -(\lambda-3)(\lambda-2)(\lambda-1) &= 0
\end{align*} \\
\therefore \lambda = 1,2,3 det ( B − λ I ) = − λ − 1 2 − 2 1 − λ 2 − 3 − 1 5 − λ = − λ 1 − λ 2 − 1 5 − λ − ( − 2 ) − 1 2 − 1 5 − λ + ( − 3 ) − 1 2 1 − λ 2 = − λ ( λ 2 − 6 λ + 7 ) − ( − 2 ) ( λ − 3 ) + ( − 3 ) ( 2 λ − 4 ) = − λ 3 + 6 λ 2 − 11 λ + 6 = − ( λ − 3 ) ( λ − 2 ) ( λ − 1 ) = 0 = 0 = 0 = 0 = 0 ∴ λ = 1 , 2 , 3
The eigenvalues of B B B are 1 1 1 , 2 2 2 , and 3 3 3 .
λ = 1 ⟹ B − I B − I = [ − 1 − 2 − 3 − 1 0 − 1 2 2 4 ] ⟹ rref ( B − I ) = [ 1 0 1 0 1 1 0 0 0 ] ∴ x 2 = − x 3 x 1 = − x 3 x 3 ∈ R ∴ ker ( B − I ) = { ( − x 3 − x 3 x 3 ) : x 3 ∈ R } = { x ( − 1 − 1 1 ) : x ∈ R } \lambda=1 \implies B-I \\
B-I = \begin{bmatrix}
-1 & −2 & −3 \\
−1 & 0 & −1 \\
2 & 2 & 4
\end{bmatrix} \implies\operatorname{rref}(B-I) = \begin{bmatrix}
1 & 0 & 1 \\
0 & 1 & 1 \\
0 & 0 & 0
\end{bmatrix} \\
\therefore x_2 = -x_3 \\
x_1 = -x_3 \\
x_3 \in\R \\
\therefore\ker(B-I) = \Set{
\begin{pmatrix}
-x_3 \\ -x_3 \\ x_3
\end{pmatrix}: x_3 \in\R
} = \Set{
x\begin{pmatrix}
-1 \\ -1 \\ 1
\end{pmatrix}: x\in\R
} λ = 1 ⟹ B − I B − I = − 1 − 1 2 − 2 0 2 − 3 − 1 4 ⟹ rref ( B − I ) = 1 0 0 0 1 0 1 1 0 ∴ x 2 = − x 3 x 1 = − x 3 x 3 ∈ R ∴ ker ( B − I ) = ⎩ ⎨ ⎧ − x 3 − x 3 x 3 : x 3 ∈ R ⎭ ⎬ ⎫ = ⎩ ⎨ ⎧ x − 1 − 1 1 : x ∈ R ⎭ ⎬ ⎫
An eigenvector corresponding to λ = 1 \lambda=1 λ = 1 is ( − 1 − 1 1 ) \begin{pmatrix}
-1 \\ -1 \\ 1
\end{pmatrix} − 1 − 1 1 .
λ = 2 ⟹ B − 2 I B − 2 I = [ − 2 − 2 − 3 − 1 − 1 − 1 2 2 3 ] ⟹ rref ( B − 2 I ) = [ 1 1 0 0 0 1 0 0 0 ] ∴ x 3 = 0 x 1 = − x 2 x 2 ∈ R ∴ ker ( B − 2 I ) = { ( − x 2 x 2 0 ) : x 2 ∈ R } = { x ( − 1 1 0 ) : x ∈ R } \lambda=2 \implies B-2I \\
B-2I = \begin{bmatrix}
-2 & −2 & −3 \\
−1 & -1 & −1 \\
2 & 2 & 3
\end{bmatrix} \implies\operatorname{rref}(B-2I) = \begin{bmatrix}
1 & 1 & 0 \\
0 & 0 & 1 \\
0 & 0 & 0
\end{bmatrix} \\
\therefore x_3 = 0 \\
x_1 = -x_2 \\
x_2 \in\R \\
\therefore\ker(B-2I) = \Set{
\begin{pmatrix}
-x_2 \\ x_2 \\ 0
\end{pmatrix}: x_2 \in\R
} = \Set{
x\begin{pmatrix}
-1 \\ 1 \\ 0
\end{pmatrix}: x\in\R
} λ = 2 ⟹ B − 2 I B − 2 I = − 2 − 1 2 − 2 − 1 2 − 3 − 1 3 ⟹ rref ( B − 2 I ) = 1 0 0 1 0 0 0 1 0 ∴ x 3 = 0 x 1 = − x 2 x 2 ∈ R ∴ ker ( B − 2 I ) = ⎩ ⎨ ⎧ − x 2 x 2 0 : x 2 ∈ R ⎭ ⎬ ⎫ = ⎩ ⎨ ⎧ x − 1 1 0 : x ∈ R ⎭ ⎬ ⎫
An eigenvector corresponding to λ = 2 \lambda=2 λ = 2 is ( − 1 1 0 ) \begin{pmatrix}
-1 \\ 1 \\ 0
\end{pmatrix} − 1 1 0 .
λ = 3 ⟹ B − 3 I B − 3 I = [ − 3 − 2 − 3 − 1 − 2 − 1 2 2 2 ] ⟹ rref ( B − 3 I ) = [ 1 0 1 0 1 0 0 0 0 ] ∴ x 2 = 0 x 1 = − x 3 x 3 ∈ R ∴ ker ( B − 3 I ) = { ( − x 3 0 x 3 ) : x 2 ∈ R } = { x ( − 1 0 1 ) : x ∈ R } \lambda=3 \implies B-3I \\
B-3I = \begin{bmatrix}
-3 & −2 & −3 \\
−1 & -2 & −1 \\
2 & 2 & 2
\end{bmatrix} \implies\operatorname{rref}(B-3I) = \begin{bmatrix}
1 & 0 & 1 \\
0 & 1 & 0 \\
0 & 0 & 0
\end{bmatrix} \\
\therefore x_2 = 0 \\
x_1 = -x_3 \\
x_3\in\R \\
\therefore\ker(B-3I) = \Set{
\begin{pmatrix}
-x_3 \\ 0 \\ x_3
\end{pmatrix}: x_2 \in\R
} = \Set{
x\begin{pmatrix}
-1 \\ 0 \\ 1
\end{pmatrix}: x\in\R
} λ = 3 ⟹ B − 3 I B − 3 I = − 3 − 1 2 − 2 − 2 2 − 3 − 1 2 ⟹ rref ( B − 3 I ) = 1 0 0 0 1 0 1 0 0 ∴ x 2 = 0 x 1 = − x 3 x 3 ∈ R ∴ ker ( B − 3 I ) = ⎩ ⎨ ⎧ − x 3 0 x 3 : x 2 ∈ R ⎭ ⎬ ⎫ = ⎩ ⎨ ⎧ x − 1 0 1 : x ∈ R ⎭ ⎬ ⎫
An eigenvector corresponding to λ = 3 \lambda=3 λ = 3 is ( − 1 0 1 ) \begin{pmatrix}
-1 \\ 0 \\ 1
\end{pmatrix} − 1 0 1 .
(ii) Diagonalize A A A and B B B .
Diagonalizing A A A
For eigenvalues λ A 1 = − 2 \lambda_{A1}=-2 λ A 1 = − 2 and λ A 2 = 5 \lambda_{A2}=5 λ A 2 = 5 , the diagonalization of A = [ 1 3 4 2 ] A= \begin{bmatrix}
1 & 3 \\
4 & 2
\end{bmatrix} A = [ 1 4 3 2 ] is
P − 1 A P = ( − 2 0 0 5 ) P^{-1}AP = \begin{pmatrix}
-2 & 0 \\
0 & 5
\end{pmatrix} P − 1 A P = ( − 2 0 0 5 )
where P P P is a matrix composed of the corresponding eigenvectors of A A A such that
P = ( − 1 3 4 1 1 ) . P = \begin{pmatrix}
-1 & \frac{3}{4} \\[.2em]
1 & 1
\end{pmatrix}. P = ( − 1 1 4 3 1 ) .
Diagonalizing B B B
For eigenvalues λ B 1 = 1 \lambda_{B1}=1 λ B 1 = 1 , λ B 2 = 2 \lambda_{B2}=2 λ B 2 = 2 , and λ B 3 = 3 \lambda_{B3}=3 λ B 3 = 3 , the diagonalization of B = [ 0 − 2 − 3 − 1 1 − 1 2 2 5 ] B=\begin{bmatrix}
0 & −2 & −3 \\
−1 & 1 & −1 \\
2 & 2 & 5
\end{bmatrix} B = 0 − 1 2 − 2 1 2 − 3 − 1 5 is
Q − 1 B Q = ( 1 0 0 0 2 0 0 0 3 ) Q^{-1}BQ = \begin{pmatrix}
1 & 0 & 0 \\
0 & 2 & 0 \\
0 & 0 & 3
\end{pmatrix} Q − 1 BQ = 1 0 0 0 2 0 0 0 3
where Q Q Q is a matrix composed of the corresponding eigenvectors of B B B such that
Q = ( − 1 − 1 − 1 − 1 1 0 1 0 1 ) . Q = \begin{pmatrix}
-1 & -1 & -1 \\\
-1 & 1 & 0 \\
1 & 0 & 1
\end{pmatrix}. Q = − 1 − 1 1 − 1 1 0 − 1 0 1 .
(iii) Find A 10 A^{10} A 10 and B 3 B^3 B 3 .
Finding A 10 A^{10} A 10
P = ( − 1 3 4 1 1 ) ⟹ P − 1 = 1 7 ( − 4 3 4 4 ) P − 1 A 10 P = ( − 2 0 0 5 ) 10 ∴ A 10 = P ( − 2 0 0 5 ) 10 P − 1 = ( − 1 3 4 1 1 ) ( − 2 0 0 5 ) 10 1 7 ( − 4 3 4 4 ) = ( 4 185 853 4 184 829 5 579 772 5 580 796 ) P = \begin{pmatrix}
-1 & \frac{3}{4} \\[.2em]
1 & 1
\end{pmatrix} \implies
P^{-1} = \frac{1}{7} \begin{pmatrix}
-4 & 3 \\
4 & 4
\end{pmatrix} \\
P^{-1}A^{10}P = \begin{pmatrix}
-2 & 0 \\
0 & 5
\end{pmatrix}^{10} \\
\begin{align*}
\therefore A^{10} &= P\begin{pmatrix}
-2 & 0 \\
0 & 5
\end{pmatrix}^{10} P^{-1} \\
&= \begin{pmatrix}
-1 & \frac{3}{4} \\
1 & 1
\end{pmatrix} \begin{pmatrix}
-2 & 0 \\
0 & 5
\end{pmatrix}^{10} \frac{1}{7} \begin{pmatrix}
-4 & 3 \\
4 & 4
\end{pmatrix} \\
&= \begin{pmatrix}
4\ 185\ 853 & 4\ 184\ 829 \\
5\ 579\ 772 & 5\ 580\ 796
\end{pmatrix}
\end{align*} P = ( − 1 1 4 3 1 ) ⟹ P − 1 = 7 1 ( − 4 4 3 4 ) P − 1 A 10 P = ( − 2 0 0 5 ) 10 ∴ A 10 = P ( − 2 0 0 5 ) 10 P − 1 = ( − 1 1 4 3 1 ) ( − 2 0 0 5 ) 10 7 1 ( − 4 4 3 4 ) = ( 4 185 853 5 579 772 4 184 829 5 580 796 )
Finding B 3 B^3 B 3
Q = ( − 1 − 1 − 1 − 1 1 0 1 0 1 ) ⟹ Q − 1 = ( − 1 − 1 − 1 − 1 0 − 1 1 1 2 ) Q − 1 B 3 Q = ( 1 0 0 0 2 0 0 0 3 ) 3 ∴ B 3 = Q ( 1 0 0 0 2 0 0 0 3 ) 3 Q − 1 = ( − 1 − 1 − 1 − 1 1 0 1 0 1 ) ( 1 0 0 0 2 0 0 0 3 ) 3 ( − 1 − 1 − 1 − 1 0 − 1 1 1 2 ) = ( − 18 − 26 − 45 − 7 1 − 7 26 26 53 ) Q = \begin{pmatrix}
-1 & -1 & -1 \\
-1 & 1 & 0 \\
1 & 0 & 1
\end{pmatrix} \implies
Q^{-1} = \begin{pmatrix}
-1 & -1 & -1 \\
-1 & 0 & -1 \\
1 & 1 & 2
\end{pmatrix} \\
Q^{-1}B^3 Q = \begin{pmatrix}
1 & 0 & 0 \\
0 & 2 & 0 \\
0 & 0 & 3
\end{pmatrix}^3
\\
\begin{align*}
\therefore B^3 &= Q\begin{pmatrix}
1 & 0 & 0 \\
0 & 2 & 0 \\
0 & 0 & 3
\end{pmatrix}^3Q^{-1} \\
&= \begin{pmatrix}
-1 & -1 & -1 \\
-1 & 1 & 0 \\
1 & 0 & 1
\end{pmatrix}
\begin{pmatrix}
1 & 0 & 0 \\
0 & 2 & 0 \\
0 & 0 & 3
\end{pmatrix}^3
\begin{pmatrix}
-1 & -1 & -1 \\
-1 & 0 & -1 \\
1 & 1 & 2
\end{pmatrix} \\
&= \begin{pmatrix}
-18 & -26 & -45 \\
-7 & 1 & -7 \\
26 & 26 & 53
\end{pmatrix}
\end{align*} Q = − 1 − 1 1 − 1 1 0 − 1 0 1 ⟹ Q − 1 = − 1 − 1 1 − 1 0 1 − 1 − 1 2 Q − 1 B 3 Q = 1 0 0 0 2 0 0 0 3 3 ∴ B 3 = Q 1 0 0 0 2 0 0 0 3 3 Q − 1 = − 1 − 1 1 − 1 1 0 − 1 0 1 1 0 0 0 2 0 0 0 3 3 − 1 − 1 1 − 1 0 1 − 1 − 1 2 = − 18 − 7 26 − 26 1 26 − 45 − 7 53